The Influence of Supervision Development and Counselling Self-Efficacy towards Trainee Counsellor Performance - Wan Jaafar, Wan Marzuki (2007)
The purpose of this study is to determine the influence of supervision development factors and counselling self-efficacy towards counsellor performance. One Hundred respondents from three universities in Malaysia were chosen through stratified sampling. Correlational research design was used in this study. Six inventories were used. The Supervisory Working Alliance-Trainee Inventory was used to measure supervisory working alliance; the Supervisor Rating Form-Short Inventory was used to measure supervisor’s social influence; the Supervision Questionnaire was used to measure satisfaction towards supervision; the Supervisee Level Questionnaire-Revised was used to measure counselling self-development level; the Counselling Self-Estimate Inventory was used to measure counselling self-efficacy; and the Counsellor Performance Inventory was used to measure counsellor performance. The data was analyzed by using the Pearson Product Moment Correlation Coefficient, Bivariate Linear Regression and Multiple Linear Regression. There was a significant relationship between supervisory working alliance and counselling self-efficacy, r = .264, p < .05. However, there was no significant relationship between supervisor’s social influence and counselling self-efficacy, r = .123, p >.05. The findings also revealed a significant relationship between satisfaction towards supervision and counselling self-efficacy, r = .301, p < .05. The result also showed a significant relationship between counselling self-development level and counselling self-efficacy, r = .674, p <. 05. A significant relationship was found between counselling self-efficacy and counsellor performance, r = .312, p <. 05. There was also a significant relationship between supervisory working alliance and counsellor performance, r = .222, p < .05. No significant relationship was found between supervisor’s social influence and counsellor performance, r = .036, p > .05. A significant relationship was found between satisfaction towards supervision and counsellor performance, r = .229, p < .05. The result also showed that there was a significant relationship between counselling self-development level and counsellor performance, r = .297, p < .05. The Bivariate Linear Regression analysis and Multiple Linear Regression analysis showed counselling self-development level being the significant predictor towards counselling self-efficacy, R2 = .454, F(1,98) = 81.399; p < .05. However, counselling self-efficacy was the significant predictor towards counsellor performance, R2 = .098, F(1,98) = 10.589, p < .05. The Findings obtained from the study can guide counsellor educators on the importance of factors such as the counselling self development and counselling self-efficacy of trainee counsellors. This is where serious attention should be given in the education and supervision of counsellors to ensure the production of good counsellors. Overall, the findings of the research give a useful implication in the counselling profession, especially in the field of counsellor education and supervision.